Branding as a development strategy tool - O. S. Sverdlikovska; A. O. Hura; D. V. Hura; S. I. Chimshit (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2024)
The key aspects of brand development and management in the contemporary business environment have been analyzed with the aim of achieving competitive advantage and success in the market. The influence of branding on the competitiveness of enterprises has been examined and its significance as a strategic tool has been demonstrated. The process of creating a corporate identity for a company manufacturing frame furniture that seamlessly integrates with the Loft style has been described. Important stages of corporate identity development have been analyzed, from the choice of name and logo to the selection of color palette and font. An analysis of the main elements of corporate identity and their impact on brand identity and attractiveness to customers has been provided. The study is aimed at furthering the development of the brand formation process in line with market needs and consumer requirements. The practical aspect of creating a corporate identity as a strategic resource aimed at addressing the challenges of positioning the company in the market, increasing brand recognition, and attracting the attention of the target audience has been discussed. This approach helps companies create a unique image and effectively compete in the modern business environment. The market analysis findings confirm the steady demand for Loft-style furniture, underlining the relevance of developing a corporate identity for companies specializing in this direction. The choice of the name “Armadio” and the use of the appropriate color palette and font allow for the creation of a unique and attractive brand image, which contributes to attracting the attention of the target audience and forming a sustainable positive image of the company in the market. The conducted research has confirmed the relevance of using visual branding elements.